Triplex ultrasound findings of chronic leg ischemia with clinical correlation - Asghar, Abdullateef A.; Al-Hilli, Mohammed (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Chronic leg ischemia commonly affects the arteries supplying the leg and mostly caused by atherosclerosis. Triplex ultrasound scanning is useful for delineating the anatomic site of disease in the lower limb in addition to the grading of the stenosis and evaluation of post-stenotic flow.Objectives: To determine the extent of vasculopathy in patients with chronic leg ischemia by using triplex ultrasound scanning and match the sonographic findings with the clinical signs and symptoms.Patients and methods: A cross sectional study from October 2009 to September 2010 was performed on 56 patients with clinical suspicion of chronic leg ischemia referring to ultrasound unit for triplex ultrasound  examination of lower limbs at Al-Shaheed Ghazi Al-Hariri Teaching Hospital in Baghdad. Patients selected randomly and consisted of 19 women and 37 men. The age ranged between 20 and 90 year. Results: The highest proportion of patients was within 60-69 year age group. Dorsalis pedis artery was the most frequently involved artery. Most of study sample revealed multi-level stenosis. Atherosclerosis was highest causative factor in chronic leg ischemia. The commonest clinical presentation of leg ischemia was intermittent claudication. Most of the patients show high-grade stenosis. Bilateral involvement is more than the unilateral, right side affected more than the left side. Diabetes mellitus considered the leading risk factor.Conclusions: Triplex ultrasound of the lower extremities is useful to diagnose anatomic location and degree of stenosis of peripheral arterial disease, which is available and low cost.